Cost‐effectiveness of a workplace‐based hypertension management program in real‐world practice in the Kailuan study - Zhou, Yan-Feng; Chen, Shuohua; Chen, Jun‐Xiang; Chen, Simiao; Wang, Guodong; Pan, Xiong‐Fei; Wu, Shouling; Pan, An (Journal of the American Heart Association, 2024)
Background - In 2009, a workplace‐based hypertension management program was launched among men with hypertension in the Kailuan study. This program involved monitoring blood pressure semimonthly, providing free antihypertensive medications, and offering personalized health consultations. However, the cost‐effectiveness of this program remains unclear. - Methods and Results - This analysis included 12 240 participants, with 6120 in each of the management and control groups. Using a microsimulation model derived from 10‐year follow‐up data, we estimated costs, quality‐adjusted life years (QALYs), life‐years, and incremental cost‐effectiveness ratios (ICERs) for workplace‐based management compared with routine care in both the study period and over a lifetime. Analyses are conducted from the societal perspective. Over the 10‐year follow‐up, patients in the management group experienced an average gain of 0.06 QALYs with associated incremental costs of $633.17 (4366.85 RMB). Projecting over a lifetime, the management group was estimated to increase by 0.88 QALYs or 0.92 life‐years compared with the control group, with an incremental cost of $1638.64 (11 301.37 RMB). This results in an incremental cost‐effectiveness ratio of $1855.47 per QALY gained and $1780.27 per life‐year gained, respectively, when comparing workplace‐based management with routine care. In probabilistic sensitivity analyses, with a threshold willingness‐to‐pay of $30 765 per QALY (3 times 2019 gross domestic product per capita), the management group showed a 100% likelihood of being cost‐effective in 10 000 samples. - Conclusions - Workplace‐based management, compared with routine care for Chinese men with hypertension, could be cost‐effective both during the study period and over a lifetime, and might be considered in working populations in China and elsewhere.